2020
DOI: 10.1371/journal.pone.0226885
|View full text |Cite
|
Sign up to set email alerts
|

A network analysis revealed the essential and common downstream proteins related to inguinal hernia

Abstract: Although more than 1 in 4 men develop symptomatic inguinal hernia during their lifetime, the molecular mechanism behind inguinal hernia remains unknown. Here, we explored the protein-protein interaction network built on known inguinal hernia-causative genes to identify essential and common downstream proteins for inguinal hernia formation. We discovered that PIK3R1, PTPN11, TGFBR1, CDC42, SOS1, and KRAS were the most essential inguinal hernia-causative proteins and UBC, GRB2, CTNNB1, HSP90AA1, CBL, PLCG1, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 70 publications
(95 reference statements)
0
7
0
Order By: Relevance
“…This is supported by CALD1's involvement in the regulation of smooth muscle contraction (including the GI tract), [66] which is reasonable to be seen, as a network analysis investigating causative proteins related to inguinal hernia showed enrichment in the regulation of actin cytoskeleton in a previous study. [65] These findings indicate the importance of gene regulation in focal adhesion, the GI tract (the contents of protrusion), and skin covering the protrusions in the pathology of inguinal hernia.…”
Section: Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…This is supported by CALD1's involvement in the regulation of smooth muscle contraction (including the GI tract), [66] which is reasonable to be seen, as a network analysis investigating causative proteins related to inguinal hernia showed enrichment in the regulation of actin cytoskeleton in a previous study. [65] These findings indicate the importance of gene regulation in focal adhesion, the GI tract (the contents of protrusion), and skin covering the protrusions in the pathology of inguinal hernia.…”
Section: Resultsmentioning
confidence: 85%
“…Given the mechanism of inguinal hernias and a previous report showing significant enrichment in the focal adhesion pathway, this finding is intriguing. [65] The partitioned heritability analysis in cell groups using LD score regression revealed enrichment in the connective/bone and gastrointestinal (GI) tissues (p-value of 00011 for connective/bone tissues and 00045 for GI tissues, see Fig. 3).…”
Section: Resultsmentioning
confidence: 99%
“…[13][14][15][16] Even though one out of four men will develop a symptomatic inguinal hernia, recently it was found that the PTPN11 protein is related to hernia development along with PIK3R1, TGFBR1, CDC42, and SOS1 proteins. 17 Hypertrophic cardiomyopathy has a prevalence of one out of 500 adults in the general population. 18 However, it is strongly associated with NSML, 4 present in up to 80% of patients with this syndrome, the highest rate among the RASopathies.…”
Section: Discussionmentioning
confidence: 99%
“…We remark however that several papers use the term "harmonic centrality" to refer to a rather different centrality measure, e.g. [84,64].…”
Section: Proximity Centralitiesmentioning
confidence: 99%